Oral Cancer Prevention and Early Detection Knowledge and Practices of Illinois Dentists – A Brief Communication - Charles W. LeHew, PhD; Linda M. Kaste, DDS, PhD (Blackwell Synergy, 2007)
The purpose of the study was to assess Illinois dentists’ selfreported knowledge and practices concerning oral cancer prevention, early detection, and management as a baseline prior to conducting interventions designed to increase dentists’ capacity to detect and manage oral cancers and counsel their patients about risk reduction.